A reuse study from Niğde, Turkey: the conversion of industrial ash to geopolymer. Issue 6 (1st February 2016) - Doğan-Sağlamtimur, Neslihan; Bilgil, Ahmet; Demir, Merve; Yılmaz, Mehmet Lider; Polat, Serkan; Özen, Erol; Dördü, Halil
Abstract: Coal is used to generate power for industrial operations. Two types of industrial ashes, including fly and bottom ash, which are solid residues arising from coal burning, are dumped to the landfill of Niğde from a selected large-scale international firm named as Göknur A.Ş in Niğde, Turkey with no care for reuse. Geopolymer production was chosen from different alternatives of productive reuse of these waste materials. The properties of the geopolymers are dependent on source materials. Therefore, the first part included elemental analysis of ashes, sieve analysis of them, compacted bulk density analysis of them, and reaction affinity of them. The chemical composition of industrial ash used in this study contained Si and Al accompanied by Ca and Fe. This character has important implications on the potential for productive reuse and reaction potential of these waste materials. The second part of the research is planned to include ashes analysis for calculation of efficiency of combustible matter, experiment of obtaining samples from ashes in different thermal processes, activation of ashes with sodium hydroxide and sodium silicate, activation of ashes with Portland cements, pressure and resistance evaluations for geopolymer samples, water absorption experiment to them, and porosity experiment for them. Considering pressure and resistance, water absorption and porosity experiments, by only a few studies in the literature, higher-strengthened geopolymer is produced at temperatures of 100 and 150°C.